Know the patient first, and then follow the family. Taking charge early and long term grief-work. - Lanini, Iacopo (Rivista di Psicologia Clinica, 2013)
Thinking about disease not as an isolated event of existence, but as an original and personal experience of each specific context, is supported the objective of  "taking care" of cancer patient for whom it is not possible healing, but also of family and social networks. In this sense is intended Palliative Care. This article presents an experience of psychological function activated at the Unit of Palliative Care - Lenitherapy (UCP-L) of the Health Florence, in the not-for-profit service, in Tuscany, the Italian Foundation of Lenitherapy (FILE).